An All-Optical Microwave Frequency Divider with Tunable Division Factors Based on DP-DPMZM - Kunpeng Zhai; Xuhua Cao; Sha Zhu; Huashun Wen; Yinfang Chen; Ya Jin; Xinyan Zhang; Wei Chen; Jiabin Cui; Ninghua Zhu (Photonics, 2023)
Based on a dual-polarization dual-parallel Mach–Zehnder modulator (DP-DPMZM), an all-optical frequency divider is proposed and experimentally demonstrated. Two radio frequency (RF) signals are modulated on an optical carrier to work as a dual-beam master laser (ML). The optical signals of the ML are injected into a distributed feedback (DFB) laser to initiate the period-two (P2) state oscillation. By beating the output of the slave laser (SL) via circulator in a photodetector, a frequency divider with tunable factors can be achieved. The innovation of the scheme lies in having a simple structure and only requires optical devices, which is operated in wide RF frequency range without any electrical amplifiers before the photodetector to increase the conversion gain. Experiment results also demonstrate that the frequency division factors can be adjusted.